Numerical simulation of neutron flow exposure on the organic tissues - Dovbnya, A.N.; Tsymbal, V.A.; Stoyanov, A.F. (Вопросы атомной науки и техники, 2015)
The algorithm of numerically modeling of the impact of the portable neutron generator (PNG) neutron flux on organic tissue is developed and implemented, we used water phantom as a model object. The algorithm for calculating the characteristics of movement and absorption of neutrons and the absorbed dose is based on the Monte Carlo method. It is shown that the main part of the dose is absorbed in the vicinity of the neutron source (at ~1.5…2 cm), this fact makes it possible to effectively treat certain cancers.